The regime of seaports in Ukraine: a complicated way to updating legal regulation - Serhii Andrushchenko (Lex Portus, 2020)
The article outlines the advantages and disadvantages of the current legislation of Ukraine in the field of establishing the legal regime of seaports. The documents of long-term strategic planning in the maritime sphere, international agreements and sectoral (port) legislation are analyzed. It is determined that neither the program documents of the maritime sphere of Ukraine, nor other national legislation of the port sphere contain generalized norms on the regimes of seaports, but outline their components. The first indicates the need and ways to improve them, and the second – these components are regulated in detail and clearly specified, comprehensively characterize the established regimes of seaports, but only from the standpoint of domestic law, not taking into account international (bilateral) agreements on merchant shipping. At the same time, these agreements determine one of the largest elements of the integrated regime of seaports – the regime of ships under foreign flags and the regime of their crews. The author proposes to amend the current legislation of Ukraine in the field of port activities and indicate in it the determinism of the regimes of seaports of Ukraine not only of domestic legislation but also of the rules of bilateral agreements on merchant shipping. It is also noted that such norms can be enshrined in the future law of Ukraine on inland waters, the territorial sea and the continental shelf.